High-fidelity entanglement between a trapped ion and a telecom photon via quantum frequency conversion - Matthias Bock (Nature Portfolio, 2018)
Entanglement between photons and stationary quantum nodes is a fundamental resource for quantum communication, but typical transition wavelengths are far from the telecom band. Here, the authors deal with the problem using polarisation-independent, entanglement-preserving frequency conversion.